The reliability of a single-trial measurement of maximal accumulated oxygen deficit determined via perceptually-regulated exercise - Glaister, M.; Liddell, A.; Estlea, K. (Research Quarterly for Exercise and Sport, 2024)
Purpose The aim of this study was to evaluate the reliability of a single-trial determination of maximal accumulated oxygen deficit (MAOD) achieved via the aid of perceptually-regulated incremental exercise.